(untitled) (Malaysian Management Journal, 1999)
This study attempts to investigate the extent to which the financial characteristics of firms are related to institutional shareholdings. The primary motivation to carry out the study comes from an earlier paper by Hessel and Norman (1992), which showed that seven financial ratios discriminated between strongly-held and institutionally-neglected firms. As an extension of the study, the present study seeks to investigate the seven financial ratios among Malaysian companies by identifying differences in the means of the seven ratios between a group of companies with substantial institutional shareholdings against another group of companies with negligible institutional shareholdings. The findings, from a sample of KLSE listed companies, broadly support the findings by Hessel and Norman (1992), in which firms with significant institutional shareholdings exhibited a significantly higher profitability ratio against firms that were neglected by institutional investors.. This suggested that institutional investors placed greater emphasis on a firm’s short-term results. Our evidence also did not indicate institutional shareholders’ direct involvement in ensuring a firm’s long-term growth and competitiveness, as shown by the insignificant differences in the mean of growth ratio between firms that had significant institutional shareholdings and those that were neglected by institutional investors.